Mrs Fenomena Influencer Muslim dan Otoritas Penafsiran Al-Qur’an di Era Digital: Kajian atas Pergeseran Otoritas Keagamaan di Media Sosial - Karimatul Ma'rifat, Aulia (LPPI Universitas Al-Qolam Malang, 2025)
This study explores the phenomenon of Muslim influencers on social media and how they claim and construct authority in interpreting the Qur’an in the digital age. With the rise of digital platforms such as YouTube, Instagram, and TikTok, influencers from religious scholars to public figures actively share Islamic content, including interpretations of Qur’anic verses. The objective of this research is to examine how these influencers engage in the practice of Qur’anic interpretation and to analyze the shift in interpretive authority from traditional scholars to digital public figures.The study employs a qualitative approach using online observation methods to analyze digital content produced by Muslim influencers. The data is interpreted based on typologies of religious authority and levels of influence on social media. The findings indicate that social media has become a new arena for negotiating religious authority. Interpretive authority, which was once exclusive to formally trained scholars, has become more open and shaped by popularity and audience engagement. On the other hand, social media has also contributed to the emergence of new forms of interpretation, such as visual tafsir, which are more communicative and accessible to the public. This phenomenon calls for collaboration between scholars, academics, and digital practitioners to ensure that disseminated religious messages remain authentic and responsible. Keywords: Muslim Influencers, Religious Authority, Digital Tafsir